Nasal polyps with osseous metaplasia: A misunderstood situation. Issue 8 (22nd May 2020) - Mat, Quentin; Mehta, Rupal; Tainmont, Sophie; Duterme, Jean‐Pierre
Abstract: Osseous metaplasia in nasal polyps is rare but benign. To exclude dangerous lesions, sending the entirety of histological samples is mandatory in cases presenting with clustered densities on CT scan. Microdebrider should not be used for this surgery. Abstract : Osseous metaplasia in nasal polyps is rare but benign. To exclude dangerous lesions, sending the entirety of histological samples is mandatory in cases presenting with clustered densities on CT scan. Microdebrider should not be used for this surgery.